2018
DOI: 10.1002/adfm.201802520
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Polymer:PCBM Thin Films under Competitive Illumination and Thermal Stress

Abstract: The combined effects of illumination and thermal annealing on the morphological stability and photodimerization in polymer/fullerene thin films are examined. While illumination is known to cause fullerene dimerization and thermal stress their dedimerization, the operation of solar cells involves exposure to both. The competitive outcome of these factors with blends of phenyl-C61-butyric acid methyl ester (PCBM) and polystyrene (PS), supported on PEDOT:PSS is quantified. UV-vis spectroscopy is employed to quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 46 publications
1
47
0
Order By: Relevance
“…Mixture thermodynamics and interfacial width. PS has been extensively studied in bulk, near surfaces/interfaces and in thinfilms (e.g., the dependence of the glass transition temperature on Mw 40 and film thickness 41 ), and we have previously utilised this polymer to understand morphological development during OPV fabrication and operation [42][43][44][45] . As part of a recent study on fullerene crystallisation, we uncovered rapid mixing in PS/phenyl-C60-butyric acid methyl ester (PCBM) bilayers in the limit of high PS Mw, well before crystallisation of the fullerene 43 .…”
Section: Resultsmentioning
confidence: 99%
“…Mixture thermodynamics and interfacial width. PS has been extensively studied in bulk, near surfaces/interfaces and in thinfilms (e.g., the dependence of the glass transition temperature on Mw 40 and film thickness 41 ), and we have previously utilised this polymer to understand morphological development during OPV fabrication and operation [42][43][44][45] . As part of a recent study on fullerene crystallisation, we uncovered rapid mixing in PS/phenyl-C60-butyric acid methyl ester (PCBM) bilayers in the limit of high PS Mw, well before crystallisation of the fullerene 43 .…”
Section: Resultsmentioning
confidence: 99%
“…[17] Recently, we reported a neutron reflectivity study on the competitive effects of light and temperature on the morphological stability of a polymer:fullerene blend. [18] These results found PCBM dimers to be effectively immobile compared to PCBM monomers in the blend matrix. The impact of PCBM dimerization on OSC performance appears thus nontrivial, and quantifying the PCBM dimer population throughout the processing steps, at both short-and long-term operation conditions, is important to predict and improve OSC stability.The photochemical dimerization (and polymerization) of C 60 fullerenes was reported two decades ago by Eklund and co-workers, [19] who found crosslinking of up to 20 molecules upon photoirradiation of neat fullerene films.…”
mentioning
confidence: 88%
“…Upon illumination in an inert (N 2 ) atmosphere, PCBM dimerization results in a spectral UV-vis absorbance feature, that has been previously documented. [12,18] Figure 2a presents the absorbance of a PCDTBT:PCBM 1:2 thin film during 50 h illumination at 630 W m −2 from a white LED (spectrum in Figure S1, Supporting Information). Other methods used to quantify PCBM dimerization have several disadvantages: in Raman spectroscopy (visible, UV, and even near IR), for instance, the illumination itself causes dimerization and thus is convoluted in the measurement outcome; [32] high performance liquid chromatography (HPLC) requires redissolution of the thin film (often with sonication) which can potentially cause both agglomeration and dedimerization; [13] it is also comparatively time intensive.…”
Section: Absorbance Feature Calibrationmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, spinodal de‐mixing has been shown to be responsible for the complex initial burn‐in degradation of OPV devices. Other studies have also identified different origins of burn‐in degradation including polymer molecular weight,crystallinity, fullerene dimerization and degradation, and interlayer interfaces . Thus, a comprehensive study of BHJ unifying both efficiency and operational stability is of utmost importance.…”
Section: Introductionmentioning
confidence: 99%